2017
DOI: 10.1016/j.canlet.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA signature in circulating exosomes is superior to exosomal glypican-1 levels for diagnosing pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a deadly malignancy that often presents clinically at an advanced stage and that may be confused with chronic pancreatitis (CP). Conversely, CP may be misdiagnosed as PDAC leading to unwarranted pancreas resection. Therefore, early PDAC diagnosis and clear differentiation between PDAC and CP are crucial for improved care. Exosomes are circulating micro-vesicles whose components can serve as cancer biomarkers. We compared exosomal glypican-1 (GPC1) and microRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
257
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(264 citation statements)
references
References 52 publications
5
257
0
2
Order By: Relevance
“…As such, exosomes from the serum of patients emerged as an attractive approach to possibly detect cancerous lesions and monitor and predict outcome of cancer patients. Several studies have reproduced our original findings related to enrichment of GPC1 in cancer exosomes, including in breast cancer exosomes, colorectal, esophageal and pancreas cancer [2][3][4][5]8,[18][19][20] (Table 1). Additionally, most of these reports show that such enrichment of GPC1 in exosomes can serve as biomarker.…”
Section: Introductionsupporting
confidence: 70%
“…As such, exosomes from the serum of patients emerged as an attractive approach to possibly detect cancerous lesions and monitor and predict outcome of cancer patients. Several studies have reproduced our original findings related to enrichment of GPC1 in cancer exosomes, including in breast cancer exosomes, colorectal, esophageal and pancreas cancer [2][3][4][5]8,[18][19][20] (Table 1). Additionally, most of these reports show that such enrichment of GPC1 in exosomes can serve as biomarker.…”
Section: Introductionsupporting
confidence: 70%
“…Sohn W's studies revealed that the levels of circulating exosomal miR-181, miR-221, and miR-224 were significant higher in HCC patients than in chronic hepatitis B patients; however, there were little differences in the level of circulating miRNAs between these two groups [67]. The level of circulating exosomal miR-10b and miR-30c was significantly elevated in 29 PDAC patients relative to chronic pancreatitis patients; however, the level of CA 19-9 was normal or slightly increased in 8 cases [68]. Goto T's study showed that circulating exosomal miR-191, miR-21, and miR451a levels were superior to circulating miRNA levels for differentiating PDAC patients from intraductal papillary mucinous neoplasm (IPMN) patients [69].…”
Section: Discussionmentioning
confidence: 84%
“…Thus far, ex-miR-181a has been identified in exosomes derived from breast cancer cells [63], dendritic cells [64], T cells (T cell line J77) [64], stem cells [65, 66], and esophageal cancer cells [67]. It was also found in serum exosomes of patients with ovarian cancer, pancreatic ductal adenocarcinoma, and thyroid cancer [68-70]. ex-miR-181a was found to be one of the twenty most abundant human plasma exosomal miRNAs [71].…”
Section: Extracellular Mirna (Ex-mirna) and Ex-mir-181amentioning
confidence: 99%